Analysis for Science Librarians of the 2017 Nobel Prize in Physiology or Medicine: The Life and Work of Jeffrey C. Hall, Michael Rosbash, and Michael W. Young. Issue 1 (2nd January 2018) - Gilman, Neyda V.
ABSTRACT: Jeffrey C. Hall, Michael Rosbash, and Michael W. Young are the 2017 Nobel Prize in Physiology or Medicine Laureates, having earned the award for their "discoveries of molecular mechanisms controlling the circadian rhythm." They identified the genes involved in the circadian rhythm mechanism and explained how all of the different pieces of the mechanism work together. These discoveries explain how the biological cycles of Earth's organisms correspond to the rotation of the planet, acting as an inner clock. Their research also provides further opportunities to continue learning about the role of circadian rhythm and its relationship to human health ( Nobelprize.org 2017a) .